2007
DOI: 10.1021/jp074963x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Catalytic Application of Nanostructured Silver Dendrites

Abstract: We demonstrate a simple templateless and surfactant-free wet-chemical method of preparing silver (Ag) nanostructures with different dendritic morphologies at room temperature. This has been accomplished by aging the aqueous mixture of AgNO3 and citrate salts, carrying different cations for different time periods. Transmission electron microscopic (TEM) and X-ray diffraction (XRD) studies confirmed the formation of single-crystalline dendritic Ag nanostructures. It has been found that the nature and the concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
181
6
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 299 publications
(198 citation statements)
references
References 52 publications
8
181
6
3
Order By: Relevance
“…5a shows time-dependent UV-Vis spectra of Ag/CM aqueous suspensions containing 1.010 -2 NaBH 4 , after injection of 4-nitrophenol; spectra have been corrected by the scattering contribution in the microsphere suspension [56]. A maximum at 400 nm is characteristic of 4-nitrophenolate ions [54,55,57,58]; the peak decreased rapidly after injection into the Ag/CM : NaBH 4 suspension, indicating that the arylnitro group is consumed over time. The graph also shows the appearance of a peak at 290 nm, which is attributed to the formation of 4-aminophenol [54,55,57,58], thus confirming that the nitroaromatic compound is reduced to its corresponding arylamine.…”
Section: Reduction Of 4-nitrophenol Using Ag/cm Compositesmentioning
confidence: 99%
See 3 more Smart Citations
“…5a shows time-dependent UV-Vis spectra of Ag/CM aqueous suspensions containing 1.010 -2 NaBH 4 , after injection of 4-nitrophenol; spectra have been corrected by the scattering contribution in the microsphere suspension [56]. A maximum at 400 nm is characteristic of 4-nitrophenolate ions [54,55,57,58]; the peak decreased rapidly after injection into the Ag/CM : NaBH 4 suspension, indicating that the arylnitro group is consumed over time. The graph also shows the appearance of a peak at 290 nm, which is attributed to the formation of 4-aminophenol [54,55,57,58], thus confirming that the nitroaromatic compound is reduced to its corresponding arylamine.…”
Section: Reduction Of 4-nitrophenol Using Ag/cm Compositesmentioning
confidence: 99%
“…A maximum at 400 nm is characteristic of 4-nitrophenolate ions [54,55,57,58]; the peak decreased rapidly after injection into the Ag/CM : NaBH 4 suspension, indicating that the arylnitro group is consumed over time. The graph also shows the appearance of a peak at 290 nm, which is attributed to the formation of 4-aminophenol [54,55,57,58], thus confirming that the nitroaromatic compound is reduced to its corresponding arylamine. Control experiments confirmed that no reduction takes place in the presence of NaBH 4 or carbon microspheres alone, but only when Ag/CM composite particles were used in suspension.…”
Section: Reduction Of 4-nitrophenol Using Ag/cm Compositesmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, many chemists and physicsts have worked with growing interest on silver and doped silver clusters [3 -7]. The major reason is due to the fact that they exhibit unique size and shape dependence and have promising applications in many areas such as chemical sensing [8], catalysis [9,10], photochemical [11], absorbing organic materials, and heliotechnics [12,13], as well as nanofabrication [14].…”
Section: Introductionmentioning
confidence: 99%